Characteristics of Non-Alcoholic Fatty Liver Disease Patients at Dr. M. Djamil General Hospital Padang - Husna Yetti; Nada Utami Prahastiwi; Restu Susanti; Eva Decroli; Saptino Miro (The Indonesian Society for Digestive Endoscopy, 2020)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is emerging as chronic liver disease, both in developed and developing countries. NAFLD affects up to 25% population worldwide. The incidence of NAFLD associated with various risk factors supporting the development of the fatty liver. This study aim is to know the characteristics of NAFLD patients.Method: Retrospective study was conducted from medical records to find the characteristics of patients diagnosed with NAFLD at Dr. M. Djamil General Hospital from January 2016 – December 2018.Results: Seventy-seven patients were diagnosed with NAFLD. The majority of NAFLD patients were male and female at 36-45 years old and female at 65 years old. Unemployed females were more prevalent compared to males. Dyslipidemia was the most component of a metabolic syndrome found in NAFLD patients. From laboratory findings, 55.56% of patients have increased aspartate aminotransferase (AST) levels, while 52.78% have increased alanine aminotransferase (ALT) levels. Ultrasonography used widely as a diagnostic device to detect NAFLD. Pharmacological therapy based on American Asociation for the Study of Liver Disease (AASLD) recommendation that used widely to treat patients with NAFLD was statin.Conclusion: The incidence of NAFLD was found to vary in different age ranges and sexes. Dyslipidemia occurred in most of NAFLD patients. AST and ALT levels increased in about half of the patients. Abdomen ultrasound as a diagnostic modality that was widely used.